Functional Areas of Business Information System: An Analysis with Respect to Indian Organizations: Enhancing Competitiveness and Efficiency through Business Information Systems in Indian Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
During the development of a competitive worldwide environment, there is extensive pressure on most companies to make their operational, strategic, and vital process progressively productive and powerful. An information system is a collection of factors which can expand the competitiveness and better data for decision making. Thus, various organizations choose information system to improve the adequacy and productivity of their organizations.